Test Methods for the Post-cracking Behavior of the FRC in Tension: A State of the Art Review - Pedro Paulo Martins de Carvalho; Rodrigo de Melo Lameiras (International Journal of Concrete Structures and Materials)
Abstract The knowledge of post-cracking tensile behavior is crucial for the proper use of Fiber-Reinforced Concrete (FRC) in engineering. Although various tests are used to determine FRC’s Mode I fracture behavior, each has its limitations in accurately predicting how FRC performs in real-world structures. This underscores the need for further research in this area. The different test methods examined have specific details that can significantly affect results, such as differences in tools, sample sizes and shapes, notch types, and how loads are applied. This paper thoroughly reviews these test methods and discusses their specific characteristics to evaluate FRC’s post-cracking behavior. It also explores the inverse analyses procedures for estimating direct tensile behavior from indirect tests and compares results from different test methods.